Community engagement to develop a dialogue-drama on adolescent pregnancy in a marginalised migrant population on the Thailand-Myanmar border: an ethnographic approach to participatory action research - Saw San Soe; Saw Thwe Paw; Mu Lwel Tha Dah; Day Mu Dah; Thae Thae Naing; K Mwee Hser; Solomon Naw; Htet Khaing Lu; Kanjana Winyoorat; Primprapaporn Thongdee; Saw Win Tun; Poe Poe; et al. (Taylor & Francis Group, 2024)
Background Communities in which adolescent pregnancy and safe abortion care are taboo may benefit from culturally appropriate information, education, and communication. Objective This ethnographic and participatory action research (PAR) elicited community members' perceptions to adolescent pregnancy: which then informed dialogue-drama development in Burmese and Karen language for undocumented migrants on the Thailand-Myanmar border. Methods PAR was conducted in Karen and Burmese language. Interviews and discussions elicited perceptions of community members about adolescent pregnancy. These were analysed for themes and using the fishbone technique, to determine the objectives for the drama. After developing the structure and content of the drama it was piloted, revised, and performed in communities. Responses and impact of the drama were recorded. The team reflected on the drama as a method for health messaging. Results In 2022, themes of responsibility, communication, and experiences of adolescent pregnancy emerged from 10 interviews and 6 discussions with community members. The fishbone technique established three dramatic objectives, woven into a teenage love story with an unplanned pregnancy, to raise community awareness of i) adolescent pregnancy, ii) contraception, and iii) choice in unexpected pregnancy. Post-drama feedback from 11 migrant communities (1,238 participants) was positive although some community members voiced concerns. Given the logistical challenges of conducting the drama in person, a film will be created for wider dissemination. Conclusions Participatory action research resulted in a culturally-nuanced performance, with communities requesting further performances and awareness on adolescent pregnancy and safe abortion care. Video is likely to be a more sustainable option.